Media in the Age of Artificial Intelligence: Theoretical Approaches and Contemporary Applications - University of Wasit / College of Arts, Media Department (lark, 2026)
The conference aimed to enhance scientific research and knowledge exchange in media studies by providing an interactive academic environment that brings together researchers, practitioners, and experts. This platform facilitated discussions on the latest theoretical and practical trends, analyzed technical and ethical challenges, and proposed actionable strategies to improve media performance and support sustainable development pathways.
Keywords: Digital media, applications